Gerakan Pencerahan (Aufklarung) dalam Islam: Menguak Islamisasi Ilmu Pengetahuan Sayed Naquib al-Attas - Bistara, Raha (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This article wants to explain how the concept of Islamization of science as Aufklarung for Muslims. The spread of secularism in the Islamic world has brought Muslims under the dichotomy of the West. They are trapped by Western knowledge which is skeptical on the basis of rationalism and empiricism. This epistemology is not in accordance with the spirit, the scientific spirit of Muslims. Muslims have their own epistemology of knowledge based on the principles of Islamic teachings from the Qur'an and Sunnah and the spirit of divine knowledge. Therefore Sayed Naquib al-Attas developed the concept of Islamization of science as an enlightener (Aufklarung) for Muslims. By using the library research method and using primary sources in the form of the original work of Sayed Muhammad Naquib al-Attas and secondary sources that support this research. The research is expected to answer the concept of Islamization of knowledge as an era of enlightenment (Aufklarung) which was developed by al-Attas. This Islamization becomes the basis of Islamic knowledge that must be disseminated by every individual Muslim, because they are all responsible for Islamic knowledge. Because with this enlightenment movement, Muslims will be independent and find themselves in accordance with the spirit of Islamic principles that do not follow Western knowledge. With the Aufklarung movement, throught the discourse cam develop Muslim personalities so that Muslims can give birth to goodness, Justice, and The strength of faith.